2005
DOI: 10.1002/arch.20065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology of the invertebrate dopamine receptors

Abstract: Dopamine is found in the nervous systems of both vertebrates and invertebrates. However, the specific actions of dopamine depend on the dopamine receptor type that is expressed in the target cell. As in mammals, different subtypes of dopamine receptors have been cloned and characterized from invertebrates, and these receptor subtypes have different structural and functional properties. Understanding how these receptors respond to dopamine and in which cells each receptor type is expressed is key to our underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
132
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(147 citation statements)
references
References 58 publications
12
132
3
Order By: Relevance
“…However, the effects of these drugs are clearly different from the pattern described in the literature (Bertorello and Katz, 1995;Missale et al, 1998;Therien and Blostein, 2000;Asghar et al, 2001;Mustard et al, 2005). In the gills of C. granulatus, domperidone and spiperone, which are known D2 antagonists in vertebrates, seem to function as D1-like antagonists, since they produce the same effect as the one produced by the PKA inhibitor KT5720, a total blockade of the DA-induced stimulation of V te .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, the effects of these drugs are clearly different from the pattern described in the literature (Bertorello and Katz, 1995;Missale et al, 1998;Therien and Blostein, 2000;Asghar et al, 2001;Mustard et al, 2005). In the gills of C. granulatus, domperidone and spiperone, which are known D2 antagonists in vertebrates, seem to function as D1-like antagonists, since they produce the same effect as the one produced by the PKA inhibitor KT5720, a total blockade of the DA-induced stimulation of V te .…”
Section: Discussionmentioning
confidence: 65%
“…However, these authors have not discussed their results in terms of receptor subtypes. It must be taken into account that in the few DA receptors characterized in invertebrates, particularly in insects, spiperone is effective to inhibit the D1-like response at molar concentrations, as in the results of the present paper, whereas the effectiveness of this drug has been tested in only one D2-like invertebrate DA receptor, with weaker effects (Mustard et al, 2005). On the other hand, domperidone is also able to block the D1-like response in C. granulatus but is not effective on the insect D1-like receptor AmDop2 (Mustard et al, 2005).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The opposing actions of DA 1 and DA 2 receptors were characterized in the mollusc Lymnaea almost 30years ago (Stoof et al, 1984), and newer cell-molecular and pharmacological studies have suggested the presence of at least three classes of DA receptors in invertebrates (Mustard et al, 2005). In the lobster stomatogastric nervous system, DA has been shown to be an important modulator altering motor pattern expression (Ayali and Harris-Warrick, 1999;Mullins et al, 2011;Vidal-Gadea et al, 2011).…”
Section: Implication Of Multiple Da Receptor Subtypesmentioning
confidence: 99%
“…Molecular cloning studies of invertebrate receptors have established that members of specific receptor families as determined by sequence homology do not reliably recapitulate the pharmacological profile of agonist and antagonist activity determined for the homologous vertebrate receptors (Tierney, 2001;Mustard et al, 2005). For example, if a dopamine D1 receptor blocker is effective in blocking the dopamine-induced rotation response in L. stagnalis, it does not definitively mean that the response is mediated by a member of the DOP1 receptor family (dopamine D1), as opposed to one of the two other known families of invertebrate dopamine receptors (Mustard et al, 2005). Nevertheless, if it effectively blocks the dopaminergic response, it can be used to determine if the hypoxia-induced increase in rotation rate action is mediated by dopamine.…”
Section: Pharmacological Analysis Of the Hypoxia Responsementioning
confidence: 99%